Genome-Wide Identification and Comparative Analysis of Cytosine-5 DNA Methyltransferase and Demethylase Families in Wild and Cultivated Peanut - Wang, Pengfei; Gao, Chao; Bian, Xiaotong; Zhao, Shuzhen; Zhao, Chuanzhi; Xia, Han; Song, Hui; Hou, Lei; Wan, Shubo; Wang, Xingjun (Frontiers in Plant Science, 2016)
DNA methylation plays important roles in genome protection, regulation of gene expression and is associated with plants development. Plant DNA methylation pattern was mediated by cytosine-5 DNA methyltransferase and demethylase. Although the genomes of AA and BB wild peanuts have been fully sequenced, these two gene families have not been studied. In this study we report the identification and analysis of putative cytosine-5 DNA methyltransferases (C5-MTases) and demethylases in AA and BB wild peanuts. Cytosine-5 DNA methyltransferases in AA and BB wild peanuts could be classified in MET, CMT, and DRM2 groups based on their domain organization. This result was supported by the gene and protein structural characteristics and phylogenetic analysis. We found that some wild peanut DRM2 members didn't contain UBA domain which was different from other plants such as Arabidopsis, maize and soybean. Five DNA demethylase encoding genes were found in AA genome and five in BB genome. The selective pressure analysis showed that wild peanut C5-MTase genes mainly underwent purifying selection but many positive selection sites can be detected. Conversely, DNA demethylase genes mainly underwent positive selection during evolution. Additionally, the expression dynamic of cytosine-5 DNA methyltransferase and demethylase genes in different cultivated peanut tissues were analyzed. Expression result showed that cold, heat or PEG stress could influence the expression level of C5-MTase and DNA demethylase genes in cultivated peanut. These results are useful for better understanding the complexity of these two gene families, and will facilitate epigenetic studies in peanut in the future.